Lessons From Inquisitorialism - Slobogin, Christopher (2014)
The adversarial system as it is implemented in the United States is a significant cause of wrongful convictions, wrongful acquittals and â€œwrongfulâ€ sentences. Empirical evidence suggests that a hybrid inquisitorial regime would be better than the American-style adversarial system at reducing these erroneous results. This paper proposes the integration of three inquisitorial mechanisms into the American trial process â€” judicial control over the adjudication process, non-adversarial treatment of experts, and required unsworn testimony by the defendant â€” and defends the proposals against constitutional and practical challenges. While other scholars have suggested borrowing from overseas, these three proposals have yet to be presented as a package. Together they could measurably enhance the accuracy of the American criminal justice system